First hematopoietic stem cell transplantation in a child with late infantile Krabbe disease in Poland - Miśkiewicz-Migoń, Izabella; Miśkiewicz-Bujna, Justyna; Mielcarek-Siedziuk, Monika; Frączkiewicz, Jowita; Gorczyńska, Ewa; Kałwak, Krzysztof (Pediatria Polska - Polish Journal of Paediatrics, 2021)
Krabbe disease (KD) is a lysosomal storage disorder, caused by a deficiency of galactocerebrosidase (GALC) or a mutation in the prosaposin gene, which leads to psychosine accumulation. Consequently, demyelination and degradation of the nervous system occur. Newborns with early infantile Krabbe disease usually present with poor feeding, irritability, hypertonicity, deafness and visual impairment. They usually die, unless transplanted with hematopoietic stem cells (HSC) during the 1st month of life. Patients with late form KD have heterogeneous symptoms, like ataxia or spastic paresis followed by slow progression. Therapeutic options are limited and hematopoietic stem cell transplantation (HSCT) remains the only life-saving method. In this report, we describe the first HSCT in late-infantile Krabbe disease in Poland. The post-transplant period was complicated by graft versus host disease (GvHD), veno-occlusive disease (VOD), mucositis and impairment of renal function. The 5-year follow-up was uneventful, confirming clinical efficacy of the HSCT.